(untitled) (University Heart Journal, 2015)
Childhood obesity is highly prevalent in urban areas of Bangladesh but information is limited. The aim of this study was to find out the prevalence of obesity in children aged 9-11 years and raise awareness about obesity and its complications. The study was conducted in a Private English Medium school in Dhaka involving 140 students whose height and weight was measured. The BMI was calculated by software provided by Centre of Disease Control. In the present study, we showed that 50% of the students were either overweight or obese out of which26.4% were obese. Majority of those found obese or overweight consumed fast foods. In conclusion, prevalence of obesity was high in a private school, which houses children from mostly middle to high income families. Enforcing healthy eating habits amongst parents could yield better results in lowering the BMI. Further surveillance in this population is essential in verifying the impact of obesity. University Heart Journal Vol. 10, No. 1, January 2014; 23-26